2018
DOI: 10.1007/s00442-018-4154-y
|View full text |Cite
|
Sign up to set email alerts
|

Is thermal limitation the primary driver of elevational distributions? Not for montane rainforest ants in the Australian Wet Tropics

Abstract: Terrestrial ectotherms are likely to be especially sensitive to rising temperatures over coming decades. Thermal limits are used to measure climatic tolerances that potentially affect ectotherm distribution. While there is a strong relationship between the critical thermal maximum (CT) of insects and their latitudinal ranges, the nature of this relationship across elevation is less clear. Here we investigated the combined relationships between CT, elevation and ant body mass, given that CT can also be influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 77 publications
3
31
0
Order By: Relevance
“…This pattern of invariant heat tolerance and variable cold tolerance supports Brett's rule (Nowrouzi et al, 2018;Polato et al, 2018;Slatyer and Schoville, 2016). Recent work has suggested that Brett's rule applies most strongly in tropical habitats with low thermal variability (Polato et al, 2018).…”
Section: Evidence For Brett's Rulesupporting
confidence: 65%
See 1 more Smart Citation
“…This pattern of invariant heat tolerance and variable cold tolerance supports Brett's rule (Nowrouzi et al, 2018;Polato et al, 2018;Slatyer and Schoville, 2016). Recent work has suggested that Brett's rule applies most strongly in tropical habitats with low thermal variability (Polato et al, 2018).…”
Section: Evidence For Brett's Rulesupporting
confidence: 65%
“…Despite this, there have been relatively few studies looking at these principles across elevational gradients, particularly outside of tropical forest habitats (Polato et al, 2018;Sunday et al, 2019). In fact, among arthropods found across elevational gradients, support for Brett's rule has only been found in grasshoppers, ants, and aquatic insects, all in tropical systems (Arnan et al, 2014;Nowrouzi et al, 2018;Polato et al, 2018). It is crucial to increase habitat and taxonomic diversity to better understand the underlying patterns and to test the generality of macrophysiological rules (Gaston et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Especially among communities of social insects such as ants and bees, where thermoregulatory and thermophilic behaviours are widely documented (e.g. Stabentheiner & Kovac, ; Shi et al ., ), a trait‐based approach has shown that niche filtering along temperature gradients (correlated with altitude) is driven by selection on physiological response traits measuring performance (survival), such as species' upper and lower thermal limits, which were higher in warmer environments and lower in colder environments, respectively (Peters et al ., ; Bishop et al ., ; but see Nowrouzi et al ., ). The relationships between species' thermal tolerances and their altitudinal ranges were also employed to test predictions of the climatic variability hypothesis (Janzen, ), with contrasting results (see Bishop et al ., ; Nowrouzi et al ., ).…”
Section: Current Trait‐based Studies On Terrestrial Arthropodsmentioning
confidence: 97%
“…Stabentheiner & Kovac, ; Shi et al ., ), a trait‐based approach has shown that niche filtering along temperature gradients (correlated with altitude) is driven by selection on physiological response traits measuring performance (survival), such as species' upper and lower thermal limits, which were higher in warmer environments and lower in colder environments, respectively (Peters et al ., ; Bishop et al ., ; but see Nowrouzi et al ., ). The relationships between species' thermal tolerances and their altitudinal ranges were also employed to test predictions of the climatic variability hypothesis (Janzen, ), with contrasting results (see Bishop et al ., ; Nowrouzi et al ., ). Likewise, studies examining altitudinal and latitudinal patterns in the morphological and behavioural response traits of similar communities suggest that increased demands for thermoregulation in colder climates at higher altitudes or latitudes could explain the observed functional clustering of species with larger body sizes and increased pilosity (Bishop et al ., ; Osorio‐Canadas et al ., ; Peters et al ., ; Costa et al ., ), darker colour (Bishop et al ., ), as well as ground‐nesting habits and higher sociality (Hoiss et al ., ; Reymond et al ., ; but see Purcell, ).…”
Section: Current Trait‐based Studies On Terrestrial Arthropodsmentioning
confidence: 97%
“…For example, the commonly used ramping rate at 0.2–1.0°C/min may be too high compared to how species experience climate change on a daily basis, and studies have found that differences in ramping rates along with other factors including starting temperature and duration of exposure will all affect heat tolerance measurements (Rezende, Tejedo, & Santos, ; Ribeiro, Camacho, & Navas, ; Terblanche, Deere, Clusella‐Trullas, Janion, & Chown, ). Moreover, CT max is evolutionarily conserved and tends to not vary across elevational gradients (Araújo et al, ; Bishop et al, ; Nowrouzi, Andersen, Bishop, & Robson, ), while it can vary significantly even among nestmates (Cerdá & Retana, ; Ribeiro et al, ), and can also be affected by nutritional conditions (Bujan & Kaspari, ). Furthermore, some thermophilic worker ants are active at temperatures near or above CT max with behavioural adjustments including gaster raising, climbing lower vegetation and taking smaller loads to nests (Andrew, Hart, Jung, Hemmings, & Terblanche, ; Cerdá, Retana, & Cros, ; Sunday et al, ).…”
Section: Introductionmentioning
confidence: 99%